2004
DOI: 10.1002/ajmg.b.30076
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of the human frizzled 3 (FZD3) gene haplotype with schizophrenia in Chinese Han population

Abstract: Frizzled 3 (FZD3) gene is located on chromosome 8p21, a region that has been implicated in schizophrenia in genetic linkage studies. The FZD3 is a transmembrane receptor required for Wnt signal transduction cascades that have been thought to be involved in producing the cytoarchitectural defects observed in schizophrenia. Previous work has showed a strong association between FZD3 locus and schizophrenia in family-based study. To confirm this issue further, we investigated a genetic association between four sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
3
31
0
3
Order By: Relevance
“…All of the participants were Chinese Han descendants. A part of this sample has been used in our previous study [17]. The age of clinical symptoms onset (13-53 years, mean 25.67 years) was retrospectively estimated as the time of emergence of any schizophrenic symptoms according to the International Classification of Diseases-10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the participants were Chinese Han descendants. A part of this sample has been used in our previous study [17]. The age of clinical symptoms onset (13-53 years, mean 25.67 years) was retrospectively estimated as the time of emergence of any schizophrenic symptoms according to the International Classification of Diseases-10.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of 25 ml PCR reaction mixture and the condition of PCR amplification were performed to be the same as that reported in our previous study [17], with annealing temperatures of 55-621C. Fifteen microliter PCR products were digested completely with 2U of restriction enzyme (HaeIII for rs947267, BsrI for rs778294) and electrophoresed subsequently on 2-4% agarose gels stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…The human FZD3 gene is located on chromosome 8p21, a linkage locus containing a putative gene for schizophrenia (Pulver et al, 1995;Blouin et al, 1998;Kendler et al, 2000;Gurling et al, 2001). Candidate gene association studies in this region have shown that SNPs within the FZD3 gene are strongly associated with schizophrenia in Chinese Han (Yang et al, 2003;Zhang et al, 2004), as well as in Japanese descents (Katsu et al, 2003). Nevertheless, such findings remain controversial since other groups have not been able to replicate and extend these observations in other populations (Ide et al, 2004;Jeong et al, 2006).…”
Section: Schizophrenia and Polymorphisms In Frizzled 3 And Gsk3bmentioning
confidence: 99%
“…Furthermore, the studies of allele-specific single-nucleotide polymorphism (SNP) provide detailed information of disease susceptibility alleles, genotypes or haplotype transmission, regardless major or minor alleles on multiple risk loci on chromosome. 1-4 Numerous family-based linkage or population-based studies have identified a large set of schizophrenia-associated loci; however, many have not been replicated either in a different ethnic background, 5,6 or in the same ethnic background but in a diverse geographical location. 7,8 Although the number of risk loci is rather large, only a small portion overlaps with the large cumulative pool of genes that have shown changes of expression in the disease state.…”
Section: Introductionmentioning
confidence: 99%